Optimasi Rute Kunjungan Cluster Sales Officer (CSO) Menggunakan Ant Colony Optimization (ACO) - Yaputera, Irwin; Hanafi, Rosmanalia; Rusman, Muhammad (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2022)
Indosat Ooredoo Hutchison is a private company engaged in the telecommunications sector. Business processes in this company are influenced by the performance of salesmen, which in the company are called Cluster Sales Officer (CSO). CSO determines the route of visiting outlets based on experiences. However, the route taken is not optimal yet in terms of distance and travel time which contribute to cost inefficiency. This research was conducted to determine the optimal route using the Ant Colony Optimization algorithm to minimize the distance and travel time and costs. The data obtained are the coordinates and order of CSO visits on Route I (Monday, Wednesday, and Friday) and Route II (Tuesday, Thursday, and Saturday). Based on these data, the researchers then calculated the distance and travel time as well as the costs incurred on the initial CSO route. The next step is to calculate the distance and travel time as well as the costs incurred on the proposed route with the Ant Colony Optimization algorithm. The calculation results show that by using the Ant Colony Optimization algorithm, Proposed Route I which has the total distance traveled, time required, and costs incurred, obtained an efficiency of around 8% from the initial route. As for the Proposed Route II has an efficiency of around 4% is obtained from the initial route. So that the total proposed route in a month is more efficient around 6% compared to the initial route by CSO.